1985
DOI: 10.1159/000124068
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Diurnal Rhythms of Pineal Serotonin, 5-Hydroxyindoleacetic Acid, Norepinephrine, Dopamine and Serum Melatonin in the Male Rat

Abstract: Pineal serotonin (5-HT), 5-hydroxyindoleacetic acid (5-HIAA), norepinephrine (NE) and dopamine (DA) were measured by high-pressure liquid chromatography with electrochemical detection and serum melatonin was measured by radioimmunoassay in rats aged 3 weeks, 8 weeks and 18 months. They were killed either at mid-light or mid-dark of a 12 h light:12 h dark cycle. Diurnal rhythms were observed for 5-HT and 5-HIAA in all ages studied while those for NE and DA were not observed in the 18-month-old animals. Pineal 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…The peak of DOPAC, delayed by 2 h with respect to the nadir of DA, reflects the deamination rate of DA. These data support previous studies showing circadian changes of catecholamine levels in some regions of rat brain [5, 6, 7, 9, 31, 32, 33], and show that pinealectomy and aMT replacement therapy influence the dopaminergic but not serotonergic system in the striatum. Although some reports point to an involvement of aMT in the 5-HT turnover in some brain areas in rats [34], the lack of interaction between aMT and 5-HT in the mouse striatum agrees with other studies [35].…”
Section: Discussionsupporting
confidence: 92%
“…The peak of DOPAC, delayed by 2 h with respect to the nadir of DA, reflects the deamination rate of DA. These data support previous studies showing circadian changes of catecholamine levels in some regions of rat brain [5, 6, 7, 9, 31, 32, 33], and show that pinealectomy and aMT replacement therapy influence the dopaminergic but not serotonergic system in the striatum. Although some reports point to an involvement of aMT in the 5-HT turnover in some brain areas in rats [34], the lack of interaction between aMT and 5-HT in the mouse striatum agrees with other studies [35].…”
Section: Discussionsupporting
confidence: 92%
“…Day-night variations of pineal N E and DA content shown here are equivalent to those reported previously by using similar methodology (8,39). Diurnal rhythms of pineal catecholamine levels are probably due to the nocturnal increase of pineal sympathetic activity (4,5), which in turn causes the observed elevation of T H activity (6).…”
Section: Discussiorsupporting
confidence: 87%
“…Studies aimed at investigating the effect of aging on pineal indoleamines in rats indicated reductions in 5-HT and 5-HIAA content when assessed at two time points in the 24-hour cycle [10,12]. Our present study, including 6 time points throughout a 24-hour cycle, agrees with the existence of such a decrease in pineal 5-HT and 5-HIAA.…”
Section: Discussionsupporting
confidence: 86%
“…In aged rodents [9][10][11][12] and humans [13][14][15][16][17][18][19], decreases in pineal melatonin secretion have been documented. In addition, neuronal degeneration at the SCN [20] and a decrease in the number of pinealocytes [21] have been reported as a consequence of aging and could be relevant causes of age-related decreases in melatonin levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation